Explanation of near-death experiences: a systematic analysis of case reports and qualitative research - Hashemi, Amirhossein; Oroojan, Ali Akbar; Rassouli, Maryam; Ashrafizadeh, Hadis (Frontiers in Psychology, 2023)
Abstract Background and Objective: Some individuals report a near-death experience (NDE) after a life-threatening crisis, which refers to a range of subjective experiences related to impending death. This experience is a phenomenon with transcendental elements, which leads to deep permanent changes in both the individual and the social lives of the NDEr’s. Therefore, this study aims to review the near-death experiences of individuals with different religious and cultural views. Methodology: This is a systematic analysis study. All the case report, case series and qualitative research studies which presented patients’ NDE experiences were included in the study, without language restrictions, and in the period of 1980-2022. The stages of screening, selection, data extraction, and quality assessment have been gone through by two of the researchers. Data analysis and synthesis has been done qualitatively. JBI Critical Appraisal Checklist tool was used to evaluate the quality of the included studies. Findings: After the initial search, 2407 studies were included, 54 of which underwent final examination. The total number of the NDEr’s in the studies was 465 men, women, and children. Among these studies, 27 were case reports, 20 were case series, and 7 were qualitative studies. Near-death experiences have been categorized into 4 main categories and 19 subcategories. The main categories include emotional experiences (2 subcategories), cognitive experiences (4 subcategories), spiritual and religious experiences (4 subcategories), and supernatural experiences (9 subcategories in two categories (out of body experiences, and supernatural and metaphysical perceptions)). Conclusion: The most frequent near-death experiences were supernatural experiences, especially the experience of leaving the body. The basis and the content of the patterns mentioned by the NDEr’s are similar, and the differences are in the explanation and the interpretation of the experience. There is a common core among them such as out-of-body experiences, passing through a tunnel, heightened senses, etc. Therefore, correct knowledge of near-death experiences leads to providing helpful answers to patients.